A half century of returns on stocks and bonds : rates of return on investments in common stocks and on U.S. Treasury securities, 1926-1976 - Fisher, Lawrence; Lorie, James Hirsch (Chicago : University of Chicago Graduate School of Business, 1977)
This book applies multi period portfolio theory to the construction and re balancing of portfolios composed of U.S. stocks, corporate bonds, government bonds, and a risk-free asset, with small stocks included as a separate investment vehicle.
Bibliography: p. 173-174.
ucj, 15/01/2019
Loans
Keywords: Stocks; Bonds